Hubungan capaian program gizi dengan tingkat akreditasi puskesmas di Aceh - Junaidar Junaidar; Melania Hidayat; Hafnidar A Rani; Milza Oka Yussar (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2020)
The quality of health services is measured by 3 components, namely input (HR, Infrastructure,) process (reliability), and output (product results). If the program's achievements do not reach the target, the quality of primary health care services can be doubted. The research objective is to determine the achievements of the program with the level of accreditation of health centers. The study uses a descriptive-analytic method with a cross-sectional design, using secondary data essential nutrition programs. The population and sample are all primary health care in Aceh Province that are accredited or not accredited, data collection is carried out in the program and data section of the Aceh Health Office and the statistical tests used are chi-square and odds ratio using STATA 13 software. The results of the study indicate, that malnutrition that receives care with low performance, children under five are weighed with low performance and low LBW cases have a relationship with the level of accreditation (p-value <0,05). In conclusion, several nutrition programs related to primary health care accreditation are malnourished children receiving treatment, LBW, and weighing under five. While the achievements of other nutrition programs do not show a relationship with the accreditation of primary health care. Suggestions, to create excellently and quality service, the health center must be able to improve program achievements according to the Government's target either in accordance with one of the indicators namely the strategic plan and health indicators.